Overview of Patient Safety Culture with the AHRQ Model at General Hospital - Susanti, Eva; Efendy, Ismail; Maryanti, Endang (Hasanuddin Medan, 2023)
A healthy latrine coverage rate of 100% is the goal for the Krueng Sabee Health Center's access to proper sanitation program of the 11 villages in the Krueng Sabee Health Center's service area, 4 villages (36.36%) have access to healthy latrines, while 7 villages (63.64%) do not. The latrine ownership rate at the center is 36.36%, but this figure is still short of the target. Sampling approach used in combination study (mixed methodologies research) 95 samples were randomly selected using quantitative techniques, while 9 informants were chosen using qualitative techniques. Logistic regression tests were used to examine quantitative data on a univariate, bivariate, and multivariate basis. data that has been transformed into a qualitative form for presentation and conclusion-making. Quantitative research results: Logistic regression test results: education level OR= 3,452, income level OR= 80,695, knowledge OR= 4,717, attitude OR= 43,982 and social culture OR= 0.647, income level is the dominant independent variable that influences family latrine ownership with the OR value = 80,695. The results of the qualitative analysis show that the majority of families do not have toilets, due to low income levels. Conclusion: level of education, attitudes, social culture towards ownership. Interview results play an active role in providing information, counseling and explaining the importance of family latrine ownership. Village officials who facilitate support for latrine ownership allocate data on assistance for latrine construction in limited quantities. It is recommended that the Health Service evaluate and integrate related programs in increasing latrine coverage in its working areas.